2016
DOI: 10.1021/acs.jpca.6b04226
|View full text |Cite
|
Sign up to set email alerts
|

Ti(N5)4 as a Potential Nitrogen-Rich Stable High-Energy Density Material

Abstract: We have studied molecular structures and kinetic stabilities of M(N5)3 (M = Sc, Y) and M(N5)4 (M = Ti, Zr, Hf) complexes theoretically. All of these compounds are found to be stable with more than a 13 kcal/mol of kinetic barrier. In particular, Ti(N5)4 showed the largest dissociation energy of 173.0 kcal/mol and thermodynamic stability. This complex had a high nitrogen content (85% by weight), and a significantly high nitrogen to metal ratio (20:1) among the neutral M(N5)n species studied here and in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…In summary, we have utilized database mining and periodic DFT calculations to survey the structural landscapes of coordination frameworks based on the pentazolate ion, whose first stable compounds have just been reported. 1 , 4 , 5 Whereas earlier work has considered the pentazolate anion as a ligand that would form discrete metallocene-like complexes, 37 , 38 this computational screen is the first to investigate a different role: as a ligand in the formation of frameworks analogous to those of other azolates. The possibility of framework formation is expected not only by analogy to existing MAFs, but also based on the binding geometries of pentazolate ions in recently isolated complexes and salts, 1 , 4 , 5 as well as by structures of two cobalt complexes of a related N 6 H 2 ligand, which demonstrated a pentazole unit acting as a tetradentate ligand through four distinct nitrogen atoms (CSD codes UKEZIU, UKEZOA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we have utilized database mining and periodic DFT calculations to survey the structural landscapes of coordination frameworks based on the pentazolate ion, whose first stable compounds have just been reported. 1 , 4 , 5 Whereas earlier work has considered the pentazolate anion as a ligand that would form discrete metallocene-like complexes, 37 , 38 this computational screen is the first to investigate a different role: as a ligand in the formation of frameworks analogous to those of other azolates. The possibility of framework formation is expected not only by analogy to existing MAFs, but also based on the binding geometries of pentazolate ions in recently isolated complexes and salts, 1 , 4 , 5 as well as by structures of two cobalt complexes of a related N 6 H 2 ligand, which demonstrated a pentazole unit acting as a tetradentate ligand through four distinct nitrogen atoms (CSD codes UKEZIU, UKEZOA).…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 Our study was encouraged by the recent demonstration of the ability of periodic density-functional theory (DFT) calculations to provide a realistic assessment of topological preferences and enthalpic stability of imidazolate-based MAFs. 36 Importantly, whereas earlier theoretical work has focused on pnz – as a ligand that should form discrete molecular complexes of the metallocene type, 37 , 38 this study is the first to consider the formation of extended frameworks based on pnz – .…”
Section: Introductionmentioning
confidence: 94%
“…At present, a large number of studies have shown that metals are crucial for stabilizing cyclo‐N 5 − , and metal‐cyclo‐N 5 − salts exhibit high kinetic stability and energy content, suggesting that metal complexes of cyclo‐N 5 − have significant potential as HEDMs. [ 29–30 ] However, the currently obtained metal‐cyclo‐N 5 − salts need to be synthesized under extreme conditions of high temperature and pressure, which limit its practical application, such as Fe 3 N 2 , FeN 2 , and FeN 4 . [ 31 ] Consequently, the pursuit of metal‐cyclo‐N 5 − compounds with high energy content is an important issue related to applications.…”
Section: Figurementioning
confidence: 99%
“…However, over time, new polynitrogenated species such as N 3 , N 4 , N 5 − and N 5 + have been discovered or posited, whose synthesis has either represented a challenge or turned out to be surprisingly simple [27][28][29][30]. In spite of this, until now, the species with the highest content of nitrogen produced in measurable quantities has contained 5 nitrogen atoms, meaning that in particular the cyclopentazole anion could be considered as a motivator for theoretical studies on its formation, as well as representing a building block towards more complex structures [31][32][33][34][35]. As species with higher nitrogen content have proved to be very unstable with respect to decomposition to N 2 , theoretical studies have outnumbered experimental ones.…”
Section: Polynitrogenated Materialsmentioning
confidence: 99%